Incidence and Outcomes of Patients With Oral Cavity Squamous Cell Carcinoma and Fourth Primary Tumors: A Long-term Follow-up Study in a Betel Quid Chewing Endemic Area. Issue 12 (March 2016) - Adel, Mohamad; Liao, Chun-Ta; Lee, Li-Yu; Hsueh, Chuen; Lin, Chien-Yu; Fan, Kang-Hsing; Wang, Hung-Ming; Ng, Shu-Hang; Lin, Chih-Hung; Tsao, Chung-Kan; Huang, Shiang-Fu; Kang, Chung-Jan; et al.
Abstract : Abstract: The aim of this study was to explore the incidence and outcomes of patients with oral cavity squamous cell carcinoma (OSCC) and fourth primary tumors (PTs) in a betel-chewing endemic area. We retrospectively examined the records of 1836 OSCC patients who underwent radical tumor resection between 1996 and 2014. The outcome measures included the incidence and number of multiple PTs, the main risk factors, and their associations with overall survival (OS). Of the 1836 patients, 1400 (76.3%) had a single PT, 344 (18.7%) a second PT, 67 (3.6%) a third PT, and 25 (1.4%) a fourth PT. Univariate analyses (log-rank test) identified the following factors as significantly associated with a fourth PT: simultaneous first and second PTs, betel quid chewing, buccal subsite, and pT3–4 status. After allowance for the potential confounding effect of other risk factors, all of these factors retained their independent prognostic significance in stepwise multivariate analyses, the only exception being betel chewing. The incidences of second, third, and fourth PTs at 5 and 10 years were 20.2%/34.6%, 4.0%/8.6%, and 1.0%/2.3%, respectively. The 5 and 10-year OS rates (calculated from the diagnosis of each PTs) for patients with a single, second, third, and fourth PTs were 68%/61%, 43%/37%, 45%/39%%, and 30%/30%, respectively ( P < 0.0001). Among patients with a fourth PT, those who underwent radical surgery showed a significantly higher 3-year OS than those who did not (57% vs 13%; P = 0.0442). Fourth PTs are rarely observed in OSCC patients in a betel quid-chewing endemic area. Long-term survival rates of patients treated with radical surgery seems acceptable, being 4-fold higher than their counterparts. Abstract : Supplemental Digital Content is available in the text